Keadilan Pada Orang-Orang Kudus: Pendekatan Non-Litigasi Dalam Menyelesaikan Sengketa Berdasarkan 1 Korintus 6:1-11 - Bakhoh Jatmiko; Sherly Ester Elaine Kawengian; Novita (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
This research is motivated by various legal cases (criminal or civil) involving Christians or clergy as individuals, as well as churches or Christian foundations as a Christian institution which chooses litigation as the settlement process. Even though the legal approach is guaranteed by the constitution, the emergence of legal cases that were prosecuted by Christians has become public consumption, causing problems with the effectiveness of the marturia of God's church. Meanwhile, in the light of the Bible, litigation is not the only solution to dispute resolution. Alternative efforts that are based on Christian values ​​should be put forward as a preventive as well as a solution to the presence of problems among Christians. Therefore, this research was conducted to find alternative approaches to legal proceedings when a dispute occurs between Christians based on 1 Corinthians 6:1-11. The study uses descriptive qualitative research methods with a literature review approach to related issues, as well as the application of the principles of exegesis and hermeneutics in exploring the selected texts. The discussion presents findings that non-litigation steps can be put forward when disputes occur with a certain intensity through normative-ecclesiological, mediative and restorative approaches where dispute resolution among Christians should prioritize Bible values ​​for the glory of Christ as the head of the church.